Macroeconomic and Structural Policies to Further Stabilise the Mexican Economy - Schwellnus, Cyrille (OECD Publishing, 2011)
Improvements in the macroeconomic policy framework over the past two decades and prudent regulation of the financial system have contributed to reduce output volatility in Mexico relative to other OECD countries. The sharp recession in 2008-09 illustrated that output volatility has nonetheless remained high. The fiscal rule has helped to balance the federal budget and keep the level of government debt low, while strengthening fiscal credibility, but it could be improved further to provide a stronger buffer against shocks. Although output contracted sharply in early 2009, actual and expected inflation remained above target, in part because rigidities in product and labour markets limit price flexibility. This constrained the monetary policy response. The banking system withstood the recession of 2008-09 well, but the contraction in bank credit was sharper than in other OECD countries, in part related to a boom-and-bust cycle in consumer credit that preceded the recession. While in other OECD countries the services sector stabilises output, in Mexico it contributes to output volatility. The volatility partly reflects the dominance of services with strong links to manufacturing, while modern and more stable consumer-related services remain underdeveloped. Output volatility could be further reduced by amending the fiscal rule to accumulate larger buffers of financial assets during economic upswings or periods of high oil prices, and by taking measures to enhance the flexibility of prices. Mexico should also adopt internationally-accepted statistical conventions for its budget accounts to make them more easily comparable with those in other countries. There would be merit in moving towards macro-prudential regulation and supervision to reduce the pro-cyclicality of the financial system. Finally, entry barriers to services should be lowered to boost the development of a modern consumer-related services sector
Keywords: Economics; Mexico